Pendampingan Kelompok Tani Manise Memanfaatkan Hama Keong Mas (Pomacea sp) Sebagai Pakan Ikan Gurame (Osphronemus gouramy) - Silaban, Saronom; Rajagukguk, Juniastel; Simorangkir, Murniaty (Universitas Nusantara PGRI Kediri, 2021)
The high price of chemical fish feed is a serious problem for “Tani Manise